Site C - Fikeni, Lwandile (My University, 2019)
An unnamed man wakes up from a nightmare in the streets of Cape Town. He is homeless; and remembers that his life was not always this way; that he was once an art student in one of the elite universities in the city, with a promising career ahead of him. He begins to trace his former life to clarify the experiences that have brought him to this despairing present. With the memory of his last days among “normal” society, begins a tale of his entire life. He recalls his troubled mother whom he left in Transkei when he attended university. He is tormented by the memory of his aunt who took her life at the brink of South Africa’s democracy. As the narrator pieces together the fragments of his life, he also remembers an event that left a stain in his life when he was 6 years old. We meet his Cape Town friends Litha, Lukhanyo, and Zan. Zan is a depressed Math student who spends her days on her therapist’s couch and taking anti-depressants, which she shares with the narrator. Litha is a student filmmaker who is recruited by a group of revolutionaries who call themselves The Martyrs. And Lukhanyo, struggling to pay his university fees, finds a job at a Funeral Claims call center for a Life Insurance company where a syndicate is stealing corpses of the victims of Xenophobic attacks, to claim the insurance payout from his department. We follow the narrator and his friends from one episode to another, from bars and restaurants to art galleries and bookshops, where they steal books. Site C is a philosophical coming-of-age story about youth, identity, and memory. It is a story of a young country at odds with its initial promise and those struggling to make sense of the madness that surrounds them.
A dissertation submitted in partial fulfillment of the requirements for the award of the degree of Master of Arts in Creative Writing Faculty of Humanities University of the Witwatersrand, 2019
Keywords: Homeless persons--South Africa; Homelessness